(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: Human immunodeficiency virus (HIV), a lentivirus (member of the retrovirus family) causing acquired immunodeficiency syndrome (AIDS), weakens the immune system of the body and hence associates different opportunistic infections. Present study undertook a survey on opportunistic infections. Materials and Methods: Data were collected from both HIV carriers (CD4 count more than 250/mL of blood) and AIDS patients (CD4 count less than 250/mL of blood). Results: Analyses of the data revealed that diarrhoea, pulmonary tuberculosis, gland tuberculosis, skin lesions and fever were the common opportunistic infections. Conclusion: It can be summarized that HIV infected patients having a reduced CD4 count (<250/mL) encounter different opportunistic infections and some of these infections could be continual for long as well. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19151 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.285-291